Long-Term Patient Satisfaction and Oral Health-Related Quality of Life Following Anterior Maxillary Implant Placement: A Five-Year Follow-Up Study - Boukhris, Hanen; Zidani, Hajer; Bouslama, Ghada; Bel Haj Salah, Kawther; BenYoussef, Souha (European Journal of Dentistry, 2025)
Long-term data evaluating both patient satisfaction and oral health-related quality of life (OHRQoL) in anterior maxillary implant rehabilitation are still limited, making this investigation highly relevant. This study aimed to evaluate patient satisfaction and OHRQoL 5 years after anterior maxillary implant placement. It specifically assessed long-term satisfaction with implant-supported restorations in the aesthetic zone, the impact on OHRQoL, and key clinical and prosthetic factors influencing perceived treatment success.A prospective study was conducted at the University Hospital of Farhat Hached, Sousse, Tunisia, from March to June 2024. Eligible patients who underwent anterior maxillary implant placement between 2018 and 2019 were included. Patients with fixed implant-supported restorations and good systemic health were eligible, while those with parafunctional habits or incomplete follow-up data were excluded. Satisfaction was assessed using a Visual Analog Scale (VAS), and OHRQoL was measured using the Oral Health Impact Profile (OHIP)-14 and Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) questionnaires. A total of 50 patients participated. The sample size was determined based on an expected satisfaction rate of 80%, with a 95% confidence interval and a 10% margin of error, resulting in a required minimum of 47 participants.Data analysis was performed using SPSS version 20. Descriptive statistics summarized demographics, satisfaction scores, and OHRQoL outcomes. Inferential analyses included paired t-tests and Wilcoxon signed-rank tests to compare baseline and 5-year follow-up data. Spearman's correlation was used to examine relationships between implant-related factors and satisfaction or OHRQoL scores, while multivariate regression identified predictors of long-term satisfaction. A p-value of < 0.05 was considered statistically significant.Fifty patients (mean age: 36.5 ± 5.3 years) participated, with a 98.04% implant survival rate. At 5 years, 86.2% reported high satisfaction, with a mean VAS score of 92.8%. Phonetic outcomes received a 100% satisfaction rate, while chewing comfort and stability were also highly rated (94.0 and 93.7%, respectively). Esthetic satisfaction was reported by 85.0% of patients, and 67.5% had no difficulty maintaining hygiene. The OHIP-14 median score of 9.0 indicated minimal OHRQoL impairment. PIDAQ results showed that while most patients were satisfied with esthetics, some experienced psychosocial impacts.Five years after anterior maxillary implant placement, patients reported high satisfaction, especially regarding phonetics, chewing comfort, and esthetics. The minimal OHRQoL impact and low PIDAQ scores highlight the positive psychosocial effects of implant restorations. These results suggest that long-term evaluation of functional and psychological outcomes should be integrated into clinical decision-making and future prospective studies.
Keywords: anterior maxillary implants; five-year evaluation; implant-related quality of life; long-term follow-up; patient satisfaction